The Role of Ramadhan Flash Islamic Boarding School Activities in Shaping Students' Religious Character at Pengampelan Elementary School - Dega Sopyan; Deayu Tania Putri; Aprini Rumondang Manullang; Nabila Nabila; Muhamad Arif Hidayatullah; Maulana Dinnansyah (Global Education Journal, 2026)
One of the character values ​​that needs to be instilled from an early age is religious character. Schools play a crucial role in instilling religious values ​​through various learning and extracurricular activities. One activity frequently held in schools during Ramadan is the "Pesantren Kilat" (short Islamic boarding school) program. This study aims to determine the role of the "Pesantren Kilat" (short Islamic boarding school) program in shaping the religious character of students at Pengampelan Elementary School. The research method used was descriptive qualitative, with data collection through observation, interviews, and documentation. The results indicate that the "Pesantren Kilat" (short Islamic boarding school) program plays a significant role in shaping students' religious character, such as improving discipline in worship, fostering mutual respect, fostering honesty, and fostering behavior consistent with Islamic teachings. Furthermore, this program can foster enthusiasm for religious learning and strengthen social relationships among students and between students and teachers. Therefore, the "Pesantren Kilat" (short Islamic boarding school) program can be an effective strategy for religious character education in elementary schools.